Climate Change and Resilience Perspectives: Brazilian Museums and Their Challenges. Issue 1 (1st July 2022) - Vinicius Rosário da Silva, Marcus; Walbe Ornstein, Sheila
Abstract: Brazilian museum operations and maintenance practices, as well as collections and educational activities, can be important actors in communicating the risks of climate change and can be examples of best practice in reducing greenhouse gas emissions. Documentary research for this article was conducted with museum institutions that promote operations and maintenance best practices applicable to the sector in Brazil. As a result, Brazilian cases were assessed for greenhouse gas emission and sustainable practice metrics focusing on energy efficiency. The results still show a low Brazilian commitment by the museum sector in the combat against climate change.